ニホン ノ ナンキョク カンソク カツドウ ニオケル チリ ジョウホウ システム GIS ポータルサイト - 野木, 義史; ノギ, ヨシフミ; 北本, 朝展; キタモト, アサノブ; Nogi, Yoshifumi; Kitamoto, Asanobu (2010)
P(論文) デジタル化された空間情報を元にした地理情報システム(GIS)は,現在様々な分野で活用されている.日本南極地域観測で得られた地図データを,研究者を始め多くの人々に容易に利用可能にするため,情報・システム研究機構新領域融合研究センターの新領域融合プロジェクトのもと,南極GISポータルサイトを構築した.国土地理院および国立極地研究所が保有する南極域の地図データを,Web上で利用可能なようにデジタル化し,南極域の基礎的な空間情報がほぼ整備された.南極GISポータルサイトにより,地図を利用する基本的な作業がWeb上で行えるようになった.また,南極GISポータルサイトでは,Google Earth等のアプリケーションと連携が可能な地図データセットが提供されている.異なった種類の地図の位置データの整合性をとるという問題は残されているが,今後,南極GISポータルサイトを基礎とした,より充実した活用方法等が望まれる. GIS (Geographic Information Systems) based on digitized spatial informations have been employed in various fields recently. GIS portal site of Japanese Antarctica research has been built under the project of transdisciplinary research integration of Research Organization of Information and Systems to make good use of Antarctic map data for researchers and the public. The map data of Antarctica that the Geospatial Information Authority of Japan and the National Institute of Polar Research hold were digitized for use on the GIS portal site Web services. Fundamental spatial information on the Antarctic region was prepared, and GIS portal site of Japanese Antarctica research provides basic map operation services on the Web. GIS portal site of Japanese Antarctica research also serves data set of the map that are available for Google Earth and the other GIS application. Although the location errors of various kind of map data should be fixed, substantial use of GIS portal site of Japanese Antarctica research are expected. departmental bulletin paper